Challenges faced by youth social entrepreneurs in Malaysia: career transition to become a social entrepreneur - Che Nawi, Nur Raihan; Arshad, Mohd Mursyid; Steven, Eric Krauss; Ismail, Ismi Arif (Emerald Group Publishing, 2021)
Purpose: The practice of social entrepreneurship has grown rapidly around the world, including in Malaysia where it is still considered to be at an early stage. Nevertheless, little is known about the career transition among youth who choose careers as social entrepreneurs. The purpose of this study is to explore the challenges faced by youth social entrepreneurs who run social enterprises in Malaysia. Design/methodology/approach: This study used a qualitative approach to collect and analyse data to answer the research questions. Seven youth social entrepreneurs were interviewed until data saturation was met. An interview guide was created for the purposes of conducting the interviews. The interviews were recorded using a voice recorder. Data were transcribed verbatim and grouped in order to identify the codings, categories and themes. Findings: The findings show the career transition to become a social entrepreneur, as well as the major challenges that youth social entrepreneurs face, which include acclimatising to the life and career of a social entrepreneur and not getting support from family. Practical implications: The study findings are also significant for presenting valuable data on the experience of the developing social entrepreneur. The qualitative nature of the study provides valuable experiential insight into the lives and struggles of young social entrepreneurs in Malaysia. The findings will allow local authorities and social entrepreneurship regulatory agencies to design initiatives and plan actions intended to overcome the challenges. Originality/value: This study makes an original contribution by showing that the process of career development as a social entrepreneur has given meaning to the informants. Despite presenting many challenges, social entrepreneurship has reinforced the role of youth social entrepreneurs, especially in relation to social responsibility.